2013
DOI: 10.5999/aps.2013.40.6.666
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Plastic Surgery: A Review of Current Clinical and Translational Applications

Abstract: BackgroundStem cells are a unique cell population characterized by self-renewal and cellular differentiation capabilities. These characteristics, among other traits, make them an attractive option for regenerative treatments of tissues defects and for aesthetic procedures in plastic surgery. As research regarding the isolation, culture and behavior of stem cells has progressed, stem cells, particularly adult stem cells, have shown promising results in both translational and clinical applications.MethodsThe pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 107 publications
0
57
0
9
Order By: Relevance
“…Wound healing · Radiation therapy · Fibroblasts · Endothelial cells · Stem cells ne und Wachstumsfaktoren wird durch eine externe Bestrahlung nachhaltig gestört [14,15]. Dies kann zu einer anhaltenden entzündlichen Gewebeverän-derung mit dem Auftreten chronischer Wunden führen.…”
Section: Introductionunclassified
“…Wound healing · Radiation therapy · Fibroblasts · Endothelial cells · Stem cells ne und Wachstumsfaktoren wird durch eine externe Bestrahlung nachhaltig gestört [14,15]. Dies kann zu einer anhaltenden entzündlichen Gewebeverän-derung mit dem Auftreten chronischer Wunden führen.…”
Section: Introductionunclassified
“…Bone tissue engineering techniques with or without ASCs have been studied actively during past decades 26, 27, 28. ASCs are multipotent cells that are recognized as potentially beneficial in wide variety of medical therapies in reconstructive surgery 27, 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs are multipotent cells that are recognized as potentially beneficial in wide variety of medical therapies in reconstructive surgery 27, 28, 29, 30. The potential of these cells has evoked great enthusiasm and high expectations in both scientific and commercial circles.…”
Section: Discussionmentioning
confidence: 99%
“…In mounting experimental or pre-clinical studies, researchers found that mesenchymal stem cells (MSCs) could prevent the development of tissue fibrosis (9,10). Previously studies proved that MSCs could slow the progression of fibrosis, and reverse functional remodeling in heart, liver, kidney, and lung tissues (11)(12)(13)(14)(15). Adipose tissue-derived stem cells (ADSCs) belonged to the family of MSCs.…”
Section: Introductionmentioning
confidence: 99%